A kind of degradable adhesive tape and its preparation method and application
By using specific resins and starch combinations in the degradable tape to form a connection network structure, and improving the performance of the bonding layer by modifying monomers and surfactants, the deficiencies of the degradable tape in terms of mechanics, waterproofing and aging resistance are solved. It has achieved significant performance improvement and expansion of application areas.
Patent Information
- Application Number
- CN202410611204.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-05-16
AI Technical Summary
Existing biodegradable tapes are poor in terms of mechanical and mechanical properties, waterproof properties and aging resistance, and are difficult to meet the sustainable development needs of the express delivery industry and the tape industry.
PVC and PLA resins under specific polymerization degrees and viscosity are combined with mixed branch/amylose to form a stable connection network structure and improve mechanical and mechanical properties; the bonding layer is prepared by modifying butyl methacrylate monomer to form a three-dimensional body Multi-dimensional complex entangled structures improve aging resistance and use a mixed surfactant combination to enhance the reaction success rate and quality of the adhesive layer.
It significantly improves the waterproof, mechanical and aging resistance of biodegradable tape, solves the shortcomings of the performance of biodegradable tape on the existing market, broadens its application areas and use environment, and provides a foundation for large-scale production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of degradable adhesive tapes, and in particular to a degradable adhesive tape and a preparation method and application thereof. Background Art
[0002] With the rapid development of the express delivery industry, the sharp increase in the use of packaging products has brought a huge burden to society and the environment. Taking the simplest tape as an example, the amount of tape used by the express delivery industry each year is huge, and the total length of the tape has reached the level that it can circle the earth thousands of times. Therefore, the current environmental pressure in the field of tape is huge. At present, most of the tapes used in the industry are traditional BOPP tapes. The raw materials come from petroleum resources, which are non-renewable and increasingly depleted with the increase in usage. They are not degradable in a short time after use. After the material used completes its packaging mission, it directly becomes packaging waste, which not only aggravates white pollution, but also the separation of the carton and the plastic tape after packaging also increases the cost of recycling.
[0003] Therefore, in order to achieve sustainable development of the express delivery industry and the tape industry, the product of degradable tape came into being. However, because degradable tape is still a new product in recent years and is still in its early stages, there are still some inevitable technical problems, including the poor mechanical properties, waterproof properties, and aging resistance of degradable tape itself.
[0004] Therefore, in order to solve the above technical problems, the present application provides a degradable tape and a preparation method thereof. The degradable tape prepared in the present application can significantly improve its waterproof, mechanical and aging resistance properties while ensuring its excellent adhesion, effectively solving the performance problems of degradable tapes on the existing market, having a very good market prospect, and further broadening the application field and use environment of degradable tapes. The preparation method is simple and easy, providing a solution basis for subsequent large-scale production. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a degradable tape, which includes a degradable base layer, a degradable adhesive layer on the surface of the degradable base layer, and a release layer with a protective function on the other side of the degradable adhesive layer.
[0006] As a preferred solution, the thickness of the degradable substrate layer is 20-100 μm.
[0007] As a preferred solution, the thickness of the degradable substrate layer is 30-60 μm.
[0008] As a preferred solution, the thickness of the degradable adhesive layer is 5-50 μm.
[0009] As a preferred solution, the thickness of the degradable adhesive layer is 5-30 μm.
[0010] As a preferred solution, the thickness ratio of the degradable base layer to the degradable adhesive layer is (3.5-5.5): (0.5-2).
[0011] As a preferred solution, the thickness ratio of the degradable base layer to the degradable adhesive layer is (4-4.5):(1.2-1.5).
[0012] As a preferred solution, the thickness of the release layer is 15-30 μm.
[0013] As a preferred solution, the raw materials of the degradable base layer include, by weight: 100-150 parts of base resin, 40-60 parts of filler, 5-10 parts of lubricant, 20-40 parts of filler, and 1-10 parts of auxiliary agent.
[0014] As a preferred solution, the base resin is a composition of PVC resin and PLA resin.
[0015] As a preferred solution, the mass ratio of the PVC resin to the PLA resin is (8-12): (3-5).
[0016] As a preferred solution, the mass ratio of the PVC resin to the PLA resin is (9-10): (4-4.5).
[0017] As a preferred solution, the degree of polymerization of the PVC resin is 1100-1200.
[0018] As a preferred solution, the viscosity of the PLA resin is 4000-8000 mPa·s.
[0019] As a preferred solution, the viscosity of the PLA resin is 4500-6500 mPa·s.
[0020] As a preferred solution, the filler is a combination of amylopectin and amylose.
[0021] As a preferred solution, the mass ratio of amylopectin to amylose is (0.6-1.2):(2-4).
[0022] As a preferred solution, the mass ratio of amylopectin to amylose is (0.8-1):(3-4).
[0023] In this application, PVC, PLA resin and mixed branched / straight-chain starch are combined under specific polymerization degree and viscosity to effectively improve the mechanical properties of the whole degradable tape, and further effectively ensure its waterproof performance. The multi-walled multi-branched structure of the above-mentioned PVC and PLA resin can form a stable connection network with the added long spiral straight-chain starch structure through the bridge effect of the added branched starch structure. The existence of this structural network can not only enhance the dispersion compatibility between the resins, reduce the resistance between the multiphase interface, thereby greatly enhancing the cohesion of the system, and then under the action of external force, it can greatly improve its support and connection effect, thereby fully improving its mechanical properties. On the other hand, the above-mentioned connection network structure is easy to form a multi-network membrane structure because of the connection effect of branched starch. The existence of this structure can greatly improve the tightness between molecules, and greatly increase the circulation resistance and circulation path of water molecules in the system, thereby avoiding the hygroscopic hydrophilic phenomenon caused by the multi-hydrophilic groups caused by the addition of starch, and improving waterproof performance.
[0024] As a preferred solution, the lubricant is vegetable oil or paraffin oil.
[0025] As a preferred solution, the filler is modified zinc oxide.
[0026] As a preferred solution, the average particle size of the modified zinc oxide is 250-300 nm.
[0027] As a preferred scheme, the preparation method of the modified zinc oxide includes the following steps: S1: adding zinc oxide to a mixed solvent of water and anhydrous ethanol, then adding a silane coupling agent and stirring the mixture evenly, heating the mixture to 50-55°C, and dripping an anhydrous ethanol solution containing ethyl orthosilicate, wherein the dripping reaction time is 2-3 hours; S2: after the dripping reaction is completed, continuing the heat preservation reaction for 0.5-1.5 hours, then filtering and washing the particle product, adding the particle product to a mixed solvent of water and DMF, adding a silane coupling agent and an organic acid anhydride for a second time, heating the mixture to 60-65°C, and ultrasonically shaking the mixture for 1-3 hours, and filtering, washing, and drying the mixture after completion.
[0028] As a preferred solution, the mass ratio of zinc oxide to tetraethyl orthosilicate is (1.5-2.5):(1-2).
[0029] As a preferred solution, the average particle size of the zinc oxide is 25-50 nm.
[0030] As a preferred solution, the auxiliary agent is at least one of a stabilizer, a flame retardant, a UV resistant agent, a dispersant, a waterproofing agent, and a film-forming agent.
[0031] As a preferred solution, the raw materials of the degradable adhesive layer include, by weight: 20 to 30 parts of methyl methacrylate, 50 to 60 parts of ethyl acrylate, 5 to 10 parts of isooctyl acrylate, 1 to 10 parts of functional monomers, 0.5 to 1 part of initiator, 2 to 3 parts of salt-forming agent, 0.5 to 1 part of emulsifier, and 300 to 350 parts of solvent.
[0032] As a preferred solution, the mass ratio of methyl methacrylate, ethyl acrylate and isooctyl acrylate is (2-2.5): (5.5-6): (0.6-0.8).
[0033] As a preferred solution, the functional monomers are dicyclopentenyl acrylate and modified butyl methacrylate.
[0034] As a preferred solution, the mass ratio of the dicyclopentenyl acrylate to the modified butyl methacrylate is (1-3):(5-6).
[0035] As a preferred scheme, the preparation method of modified butyl methacrylate comprises the following steps: S1: adding ε-caprolactone, succinic anhydride and ethyl acetate into a reactor and mixing them evenly, protecting the reactor with inert gas, heating it to 60-80°C and keeping it warm for 2-3 hours; S2: after the insulation is completed, simultaneously adding ethyl acetate solution of butyl methacrylate and a reaction catalyst dropwise into the reactor, the reactor is continuously stirred at 100-200 r / min during the addition, and the dropping temperature is 80-100°C; S3: controlling the simultaneous addition of ethyl acetate solution of butyl methacrylate and the reaction catalyst, heating it to 110-130°C and keeping it warm for 3-4 hours after the addition is completed, and transferring the product to another container, adding a mixed surfactant, and stirring it evenly to obtain the product.
[0036] As a preferred solution, the mass ratio of ε-caprolactone to butyl methacrylate is (3-3.5):(2-4).
[0037] As a preferred solution, the reaction catalyst is any one of the organotin catalysts.
[0038] As a preferred solution, the mixed surfactant is a mixture of alkyl glycoside and fatty alcohol polyoxyethylene ether.
[0039] As a preferred solution, the amount of the mixed surfactant added is 5-8% of the total mass of the product in S3.
[0040] As a preferred solution, the mass ratio of the alkyl glycoside to the fatty alcohol polyoxyethylene ether is (2-3): (1-1.5).
[0041] As a preferred solution, the fatty alcohol polyoxyethylene ether is cetearyl alcohol polyoxyethylene ether.
[0042] As a preferred solution, the hydroxyl value of the cetearyl alcohol polyoxyethylene ether is 110-150 mgKOH / g.
[0043] In the present application, the degradable adhesive layer is prepared by adding the modified butyl methacrylate monomer mentioned above, which can effectively improve the degradability of the adhesive layer and improve its aging resistance. The modified butyl methacrylate monomer added in the present application has an excellent molecular structure that participates in the chemical cross-linking reaction of the degradable base layer, and can form an excellent long molecular chain entanglement effect in the adhesive system, and can greatly extend the length of the straight chain, thereby allowing the overall adhesive layer system to form a three-dimensional multi-dimensional complex entanglement structure. The existence of these structures can greatly limit the migration rate and activity of electrons and active groups in the system, thereby reducing the attraction effect on active molecules, and can effectively reduce the probability of deactivation reactions during long-term use, thereby greatly improving aging resistance; but at the same time, because the compatibility of the modified butyl methacrylate monomer with the adhesive system is reduced, and the reaction system is prone to rapid agglomeration, During the reaction process, local explosion and aggregation may occur, and the reaction may not be able to form. However, the applicant has found that the use of the mixed surfactant combination described in the present application can effectively improve the success of the reaction and ultimately improve the quality of the bonding layer. This may be because during the reaction process, the above-mentioned mixed surfactant additive can form a multi-layer encapsulation structure in the modified monomer surface system. The presence of this structure can effectively reduce its rapid agglomeration phenomenon in the reaction system, and because of the presence of its encapsulation phase, it is also very easy to form a reaction droplet phase in the reaction system. The presence of this phase can regulate the overall reaction process of the reaction, and through the affinity for different raw materials, accelerate the degree and rate of cross-linking of the modified monomer reaction, thereby effectively enhancing the various properties of the final bonding layer.
[0044] As a preferred solution, the initiator is any one of ammonium persulfate and potassium persulfate.
[0045] As a preferred solution, the salt-forming agent is triethanolamine.
[0046] As a preferred solution, the solvent is a mixed solvent of acetone and deionized water.
[0047] As a preferred solution, the mass ratio of acetone to deionized water is (1-2):(4-6).
[0048] The second aspect of the present application provides a preparation method of the above-mentioned degradable tape, which comprises the following steps: S1: adding the raw materials of the degradable base layer into a high-speed mixer and stirring and mixing them evenly, then adding the mixed materials into an internal mixer for internal mixing and plasticization, then plasticizing through an extruder, calendering and forming at 180-220°C, cooling and dividing to obtain a degradable base layer of required thickness; S2: adding methyl methacrylate, ethyl acrylate, isooctyl acrylate and a solvent into a mixture into a reactor, stirring and mixing them thoroughly, then sequentially adding a functional monomer, an emulsifier, a salt-forming agent and an initiator into the reactor for mixing and stirring, heating to 60-80°C, stirring and keeping warm for reaction for 3-5 hours, and finally neutralizing and demulsifying to obtain a degradable adhesive; S3: spraying the degradable adhesive onto the surface of the release layer, forming a degradable adhesive layer after drying, curing and aging, and compounding the degradable adhesive layer with the degradable base layer to obtain a degradable tape.
[0049] The third aspect of the present application provides an application of the above-mentioned degradable tape, including the application of the degradable tape in the fields of express logistics, food packaging, office stationery, electronic manufacturing, and disposable products.
[0050] The beneficial effects of this application are:
[0051] 1. The degradable tape provided in the present application can significantly improve its waterproof, mechanical and aging resistance properties while ensuring its excellent adhesion, effectively solving the performance problems of the degradable tapes on the existing market, and has a very excellent market prospect. It further broadens the application field and use environment of the degradable tapes, and the preparation method is simple and easy, providing a solution basis for subsequent large-scale production.
[0052] 2. A degradable tape provided in the present application effectively improves the overall mechanical properties of the degradable tape by combining PVC, PLA resins and mixed branched / amylose starch at specific polymerization degrees and viscosities, and further effectively ensures its waterproof performance; the multi-walled and multi-branched structures of PVC and PLA resins can form a stable connection network with the added long-helical amylose structure through the bridging effect of the added branched starch structure. The existence of this structural network can not only enhance the dispersion compatibility between resins and reduce the resistance between multiphase interfaces, thereby greatly enhancing the cohesion of the system, and then greatly improve its support and connection function under the action of external force, thereby fully improving its mechanical properties.
[0053] 3. A degradable adhesive tape provided in the present application has a degradable adhesive layer prepared by adding modified butyl methacrylate monomer, which can effectively improve the degradability of the adhesive layer while also improving its aging resistance; the added modified butyl methacrylate monomer has an excellent molecular structure that participates in the chemical cross-linking reaction of the degradable base layer, and can form an excellent long molecular chain entanglement effect in the adhesive system, and can greatly extend the length of the straight chain, thereby allowing the overall adhesive layer system to form a three-dimensional multi-dimensional complex entanglement structure. The presence of these structures can greatly limit the migration rate and activity of electrons and active groups in the system, thereby reducing the attraction effect on active molecules, and can effectively reduce the probability of deactivation reactions during long-term use, thereby greatly improving aging resistance.
[0054] 4. A degradable adhesive tape provided in the present application can effectively improve the reaction success and ultimately improve the quality of the adhesive layer through a specific compounded mixed surfactant combination; during the reaction process, the above-mentioned mixed surfactant additive can form a multi-layer encapsulation structure in the modified monomer surface system, and the presence of this structure can effectively reduce its rapid agglomeration phenomenon in the reaction system, and because of the presence of its encapsulation phase, it is also very easy to form a reaction droplet phase in the reaction system. The presence of this phase can regulate the overall reaction process of the reaction, and through the affinity for different raw materials, it accelerates the degree and rate of cross-linking of the modified monomer reaction, thereby effectively enhancing the various properties of the final adhesive layer. DETAILED DESCRIPTION
[0055] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0056] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0057] Example 1: Example 1 provides a first aspect of a degradable tape comprising a degradable base layer, a degradable adhesive layer on the surface of the degradable base layer, and a release layer having a protective function on the other side of the degradable adhesive layer.
[0058] The thickness of the degradable base layer is 40 μm; the thickness of the degradable adhesive layer is 15 μm; and the thickness of the release layer is 25 μm.
[0059] The raw materials of the degradable base layer include, by weight: 140 parts of base resin, 45 parts of filler, 6 parts of lubricant, 25 parts of filler and 2 parts of auxiliary agent.
[0060] The matrix resin is a composition of PVC resin and PLA resin, and the mass ratio of the two is 10:4.
[0061] The polymerization degree of the PVC resin is 1200, and it is a 170 type PVC resin product purchased from PolyOne Corporation of Japan; the viscosity of the PLA resin is 5500 mPa·s, and it is a resin product of corresponding viscosity purchased from Shanghai Yilun Plastic Chemical Co., Ltd.
[0062] The filler is a composition of amylopectin and straight-chain starch, and the mass ratio of the two is 0.8:3.5.
[0063] Amylopectin and amylose were purchased from amylopectin and amylose products sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd., respectively, with amylopectin / amylose content ≥ 70 wt%.
[0064] The lubricant is hydrogenated soybean oil, which is an auxiliary material grade hydrogenated soybean oil product purchased from Wuhan Smek Biotechnology Co., Ltd.
[0065] The filler is modified zinc oxide, and the average particle size of the modified zinc oxide is 280nm; the preparation method of modified zinc oxide includes the following steps, calculated by mass: S1: adding 2 parts of zinc oxide (average particle size 30nm) to a mixed solvent of 50 parts of water and anhydrous ethanol (the mass ratio of water to anhydrous ethanol is 4:1), then adding 1.5 parts of 3-aminopropyltriethoxysilane to the mixture and stirring evenly, heating to 55°C, and dripping 40 parts of anhydrous ethanol solution containing 2 parts of ethyl orthosilicate, and the dripping reaction time is 2.5h; S2: after the dripping reaction is completed, continue to keep warm for 1h, then filter and wash the particle product, add 2 parts of the particle product to a mixed solvent of 50 parts of water and DMF (the mass ratio of water to DMF is 4:1), add 1.5 parts of 3-aminopropyltriethoxysilane and 2 parts of succinic anhydride for the second time, heating to 65°C, ultrasonically shaking for 2.5h, filtering, washing and drying after completion.
[0066] The auxiliary agent is a stabilizer, which is a 783 type stabilizer product purchased from Nanjing Milan New Materials Company.
[0067] The raw materials of the degradable adhesive layer include, by weight: 25 parts of methyl methacrylate, 55 parts of ethyl acrylate, 8 parts of isooctyl acrylate, 7 parts of functional monomer, 0.5 parts of initiator, 2.5 parts of salt-forming agent, 1 part of emulsifier and 320 parts of solvent.
[0068] The functional monomers are dicyclopentenyl acrylate and modified butyl methacrylate, and the mass ratio of the two is 1.5:5.5.
[0069] The preparation method of modified butyl methacrylate comprises the following steps, calculated by mass: S1: adding 3.5 parts of ε-caprolactone, 2 parts of succinic anhydride and 40 parts of ethyl acetate into a reactor and mixing them evenly, the reactor is protected by inert gas, and the temperature is raised to 65°C and kept warm for 2 hours; S2: after the insulation is completed, 30 parts of ethyl acetate solution containing 3 parts of butyl methacrylate and 0.3 parts of reaction catalyst (dibutyltin dilaurate) are simultaneously added dropwise into the reactor, the reactor is continuously stirred at 150r / min during the addition, and the dropping temperature is 90°C; S3: controlling the simultaneous addition of the ethyl acetate solution of butyl methacrylate and the reaction catalyst, after the addition is completed, the temperature is raised to 120°C and kept warm for reaction for 4 hours, after the reaction is completed, the product is transferred to another container, a mixed surfactant is added, and the product is obtained after being stirred evenly.
[0070] The mixed surfactant is a mixture of alkyl glycoside and fatty alcohol polyoxyethylene ether, and the added amount of the mixed surfactant is 8% of the total mass of the product in S3.
[0071] The mass ratio of alkyl glycoside to fatty alcohol polyoxyethylene ether is 2.5:1.5; the fatty alcohol polyoxyethylene ether is cetearyl alcohol polyoxyethylene ether, which is an O-3 product purchased from Hai'an Guoyun Chemical Co., Ltd., and has a hydroxyl value of 145 mgKOH / g.
[0072] The initiator is ammonium persulfate; the salt-forming agent is triethanolamine; the emulsifier is DNS-86; the solvent of the degradable adhesive layer is a mixed solvent of acetone and deionized water, and the mass ratio of acetone to deionized water is 1:4.
[0073] The second aspect of the present embodiment provides a preparation method of the above-mentioned degradable tape, which comprises the following steps: S1: adding the raw materials of the degradable base layer into a high-speed mixer and stirring and mixing them evenly, then adding the mixed materials into a mixer for mixing and plasticizing, the mixing temperature is 200°C, the mixing time is 3 minutes, then plasticizing through an extruder, calendering at 190°C, cooling and dividing to obtain a degradable base layer of required thickness; S2: adding methyl methacrylate, ethyl acrylate, isooctyl acrylate and solvent into a mixture in a reactor, stirring and mixing them thoroughly, then adding functional monomers, emulsifiers, salt-forming agents and initiators into the reactor in turn, mixing and stirring, heating to 70°C, stirring and keeping warm for 4 hours, and finally neutralizing and demulsifying to obtain a degradable adhesive; S3: spraying the degradable adhesive on the surface of the release layer, forming a degradable adhesive layer after drying, curing and aging, and compounding the degradable adhesive layer with the degradable base layer to obtain a degradable tape.
[0074] The drying and curing temperature is 120°C, the aging temperature is 60°C, and the aging time is 80h.
[0075] The release layer was purchased from the transparent PET release film product sold by Liheng New Material Technology Co., Ltd.
[0076] Example 2: Example 2 provides a first aspect of a degradable tape comprising a degradable base layer, a degradable adhesive layer on the surface of the degradable base layer, and a release layer having a protective function on the other side of the degradable adhesive layer.
[0077] The thickness of the degradable base layer is 40 μm; the thickness of the degradable adhesive layer is 15 μm; and the thickness of the release layer is 25 μm.
[0078] The raw materials of the degradable base layer include, by weight: 135 parts of base resin, 40 parts of filler, 6 parts of lubricant, 20 parts of filler and 2 parts of auxiliary agent.
[0079] The matrix resin is a composition of PVC resin and PLA resin, and the mass ratio of the two is 9:4.5.
[0080] The polymerization degree of the PVC resin is 1200, and it is a 170 type PVC resin product purchased from PolyOne Corporation of Japan; the viscosity of the PLA resin is 5500 mPa·s, and it is a resin product of corresponding viscosity purchased from Shanghai Yilun Plastic Chemical Co., Ltd.
[0081] The filler is a composition of amylopectin and straight-chain starch, and the mass ratio of the two is 1:2.8.
[0082] Amylopectin and amylose were purchased from amylopectin and amylose products sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd., respectively, with amylopectin / amylose content ≥ 70 wt%.
[0083] The lubricant is hydrogenated soybean oil, which is an auxiliary material grade hydrogenated soybean oil product purchased from Wuhan Smek Biotechnology Co., Ltd.
[0084] The filler is modified zinc oxide, and the average particle size of the modified zinc oxide is 280nm; the preparation method of modified zinc oxide includes the following steps, calculated by mass: S1: adding 2 parts of zinc oxide (average particle size 30nm) to a mixed solvent of 50 parts of water and anhydrous ethanol (the mass ratio of water to anhydrous ethanol is 4:1), then adding 1.5 parts of 3-aminopropyltriethoxysilane to the mixture and stirring evenly, heating to 55°C, and dripping 40 parts of anhydrous ethanol solution containing 2 parts of ethyl orthosilicate, and the dripping reaction time is 2.5h; S2: after the dripping reaction is completed, continue to keep warm for 1h, then filter and wash the particle product, add 2 parts of the particle product to a mixed solvent of 50 parts of water and DMF (the mass ratio of water to DMF is 4:1), add 1.5 parts of 3-aminopropyltriethoxysilane and 2 parts of succinic anhydride for the second time, heating to 65°C, ultrasonically shaking for 2.5h, filtering, washing and drying after completion.
[0085] The auxiliary agent is a stabilizer, which is a 783 type stabilizer product purchased from Nanjing Milan New Materials Company.
[0086] The raw materials of the degradable adhesive layer include, by weight: 20 parts of methyl methacrylate, 60 parts of ethyl acrylate, 6 parts of isooctyl acrylate, 6 parts of functional monomer, 0.5 parts of initiator, 2 parts of salt former, 1 part of emulsifier and 300 parts of solvent.
[0087] The functional monomers are dicyclopentenyl acrylate and modified butyl methacrylate, and the mass ratio of the two is 1:5.
[0088] The preparation method of modified butyl methacrylate comprises the following steps, calculated by mass: S1: adding 3.5 parts of ε-caprolactone, 2 parts of succinic anhydride and 40 parts of ethyl acetate into a reactor and mixing them evenly, the reactor is protected by inert gas, and the temperature is raised to 65°C and kept warm for 2 hours; S2: after the insulation is completed, 30 parts of ethyl acetate solution containing 3 parts of butyl methacrylate and 0.3 parts of reaction catalyst (dibutyltin dilaurate) are simultaneously added dropwise into the reactor, the reactor is continuously stirred at 150r / min during the addition, and the dropping temperature is 90°C; S3: controlling the simultaneous addition of the ethyl acetate solution of butyl methacrylate and the reaction catalyst, after the addition is completed, the temperature is raised to 120°C and kept warm for reaction for 4 hours, after the reaction is completed, the product is transferred to another container, a mixed surfactant is added, and the product is obtained after being stirred evenly.
[0089] The mixed surfactant is a mixture of alkyl glycoside and fatty alcohol polyoxyethylene ether, and the added amount of the mixed surfactant is 8% of the total mass of the product in S3.
[0090] The mass ratio of alkyl glycoside to fatty alcohol polyoxyethylene ether is 2.5:1.5; the fatty alcohol polyoxyethylene ether is cetearyl alcohol polyoxyethylene ether, which is an O-3 product purchased from Hai'an Guoyun Chemical Co., Ltd., and has a hydroxyl value of 145 mgKOH / g.
[0091] The initiator is ammonium persulfate; the salt-forming agent is triethanolamine; the emulsifier is DNS-86; the solvent of the degradable adhesive layer is a mixed solvent of acetone and deionized water, and the mass ratio of acetone to deionized water is 1:4.
[0092] The second aspect of the present embodiment provides a preparation method of the above-mentioned degradable tape, which comprises the following steps: S1: adding the raw materials of the degradable base layer into a high-speed mixer and stirring and mixing them evenly, then adding the mixed materials into a mixer for mixing and plasticizing, the mixing temperature is 200°C, the mixing time is 3 minutes, then plasticizing through an extruder, calendering at 190°C, cooling and dividing to obtain a degradable base layer of required thickness; S2: adding methyl methacrylate, ethyl acrylate, isooctyl acrylate and solvent into a mixture in a reactor, stirring and mixing them thoroughly, then adding functional monomers, emulsifiers, salt-forming agents and initiators into the reactor in turn, mixing and stirring, heating to 70°C, stirring and keeping warm for 4 hours, and finally neutralizing and demulsifying to obtain a degradable adhesive; S3: spraying the degradable adhesive on the surface of the release layer, forming a degradable adhesive layer after drying, curing and aging, and compounding the degradable adhesive layer with the degradable base layer to obtain a degradable tape.
[0093] The drying and curing temperature is 120°C, the aging temperature is 60°C, and the aging time is 80h.
[0094] The release layer was purchased from the transparent PET release film product sold by Liheng New Material Technology Co., Ltd.
[0095] Comparative Example 1
[0096] The specific implementation of this comparative example is basically the same as that of Example 1, except that the mass ratio of PVC resin to PLA resin is 10:1.
[0097] Comparative Example 2
[0098] The specific implementation of this comparative example is basically the same as that of Example 1, except that the viscosity of the PLA resin is 3000 mPa·s, and the corresponding viscosity product is purchased from Hubei Xinhongyu Biomedical Technology Co., Ltd.
[0099] Comparative Example 3
[0100] The specific implementation of this comparative example is basically the same as that of Example 1, except that the degree of polymerization of the PVC resin is 1350, and the PVC resin purchased is model SG-3.
[0101] Comparative Example 4
[0102] The specific implementation of this comparative example is basically the same as that of Example 1, except that the filler is a composition of amylopectin and amylose, and the mass ratio of the two is 2:1.
[0103] Comparative Example 5
[0104] The specific implementation of this comparative example is basically the same as that of Example 1, except that the filler is a mixed particle of zinc oxide and titanium oxide, and the mass ratio of the two is 1:1.
[0105] Comparative Example 6
[0106] The specific implementation of this comparative example is basically the same as that of Example 1, except that in the preparation method of the modified zinc oxide, the average particle size of the zinc oxide is 80 nm, and the average particle size of the obtained modified zinc oxide is 400 nm.
[0107] Comparative Example 7
[0108] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional monomers are dicyclopentenyl acrylate and modified butyl methacrylate, and the mass ratio of the two is 1:1.
[0109] Comparative Example 8
[0110] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the mass ratio of alkyl glycoside to fatty alcohol polyoxyethylene ether is 5:1; the fatty alcohol polyoxyethylene ether is cetearyl alcohol polyoxyethylene ether, which is purchased from Hai'an Guoyun Chemical Co., Ltd. O-30 product sold, and has a hydroxyl value of 36~40mgKOH / g.
[0111] Performance Evaluation
[0112] Peel strength: According to the standard GB / T2792-2014, the peel strength test was carried out on the adhesive tapes prepared in the examples and comparative examples. The standard adhesive tape (25 mm*200 mm) was attached to a stainless steel plate wiped clean with alcohol, pressed back and forth with a 2 kg pressure roller, and left at room temperature for 8 hours. The test was then carried out using a peel strength tester. The measured values were taken as the average value of 10 parallel tests and recorded in Table 1.
[0113] Aging resistance: The adhesive tapes prepared in the embodiments and comparative examples were subjected to an aging resistance test. The adhesive tapes were placed in a constant temperature and humidity chamber at 75°C and 100% humidity for 7 days. The peel strength was tested and the peel strength retention rate was calculated. Peel strength retention rate (%) = peel strength after test / peel strength before test × 100%. The measured values were averaged over 10 parallel tests and recorded in Table 1.
[0114] Degradability: The degradation rates of the embodiments and comparative examples were tested with reference to the ISO 20200-2015 standard, and the degradation rates of the tapes were recorded. The measured values were taken as the average values of 10 parallel tests and recorded in Table 1.
[0115] Tensile strength: The tensile strength of the embodiments and comparative examples was tested with reference to ASTM D-638. The length of the specimen was 125 mm and the width was 12.5 mm. The measured values were averaged from 10 parallel tests and recorded in Table 1.
[0116] From the examples and comparative examples of the present application and the data results in Table 1, it can be seen that Examples 1 and 2 using the necessary technical solution of the present application can be significantly stronger than Comparative Examples 1 to 8 in terms of aging resistance, adhesion, waterproofness, mechanical properties, etc. This is mainly because Examples 1 and 2 use the correct combination of collective layer materials and adhesive layer materials to ensure the improvement of the system's own strength and the improvement of molecular compactness, strengthen the cohesion of the tape system, reduce the movement of active molecules and reaction collisions, and thus overcome the mechanical properties, waterproofness and aging resistance of the degradable tape of the prior art, and have a very excellent market prospect. However, because Comparative Examples 1 to 8 do not use the correct limiting technical solution, their performance is not comprehensive, and they are prone to have a significant gap with Examples 1 and 2 in a certain performance aspect, which further proves the necessity of the technical solution of the present application for the final technical effect.
Claims
1. A degradable tape, characterized in that: The degradable adhesive tape comprises a degradable base layer, a degradable adhesive layer on the surface of the degradable base layer, and a release layer on the other side of the degradable adhesive layer for protection; The thickness of the degradable substrate layer is 20-100 μm; The thickness of the degradable adhesive layer is 5-50 μm; The thickness ratio of the degradable base layer to the degradable adhesive layer is (3.5-5.5): (0.5-2); The thickness of the release layer is 15-30 μm; The degradable base layer comprises, by weight, 100 to 150 parts of base resin, 40 to 60 parts of filler, 5 to 10 parts of lubricant, 20 to 40 parts of filler, and 1 to 10 parts of additive; The matrix resin is a composition of PVC resin and PLA resin; the mass ratio of the PVC resin to the PLA resin is (8-12): (3-5); The polymerization degree of the PVC resin is 1000-1500; The viscosity of the PLA resin is 4000-8000 mPa·s; The filler is a composition of amylopectin and amylose; The mass ratio of amylopectin to amylose is (0.6-1.2): (2-4); The filler is modified zinc oxide; the average particle size of the modified zinc oxide is 250-300 nm; The preparation method of the modified zinc oxide comprises the following steps: S1: adding zinc oxide to a mixed solvent of water and anhydrous ethanol, then adding a silane coupling agent, mixing and stirring evenly, heating to 50-55° C., and dripping an anhydrous ethanol solution containing ethyl orthosilicate, and the dripping reaction time is 2-3 hours; S2: after the dripping reaction is completed, continuing the heat preservation reaction for 0.5-1.5 hours, then filtering and washing the particle product, adding the particle product to a mixed solvent of water and DMF, adding a silane coupling agent and an organic acid anhydride for a second time, heating to 60-65° C., ultrasonically shaking the reaction for 1-3 hours, filtering, washing, and drying after completion; The mass ratio of zinc oxide to tetraethyl orthosilicate is (1.5-2.5): (1-2); The auxiliary agent is at least one of a stabilizer, a flame retardant, a UV-resistant agent, a dispersant, a waterproofing agent, and a film-forming agent; The degradable adhesive layer comprises, by weight, 20 to 30 parts of methyl methacrylate, 50 to 60 parts of ethyl acrylate, 5 to 10 parts of isooctyl acrylate, 1 to 10 parts of a functional monomer, 0.5 to 1 part of an initiator, 2 to 3 parts of a salt-forming agent, 0.5 to 1 part of an emulsifier, and 300 to 350 parts of a solvent; The mass ratio of methyl methacrylate, ethyl acrylate and isooctyl acrylate is (2-2.5): (5.5-6): (0.6-0.8); The functional monomers are dicyclopentenyl acrylate and modified butyl methacrylate; the mass ratio of the dicyclopentenyl acrylate to the modified butyl methacrylate is (1-3): (5-6); The preparation method of modified butyl methacrylate comprises the following steps: S1: adding ε-caprolactone, succinic anhydride and ethyl acetate into a reactor and mixing them evenly, the reactor is protected by inert gas, and the temperature is raised to 60-80°C and kept warm for 2-3 hours; S2: after the heat preservation is completed, the ethyl acetate solution of butyl methacrylate and the reaction catalyst are simultaneously added dropwise into the reactor, the reactor is continuously stirred at 100-200 r / min during the addition, and the dropping temperature is 80-100°C; S3: the ethyl acetate solution of butyl methacrylate and the reaction catalyst are controlled to be added dropwise at the same time, after the addition is completed, the temperature is raised to 110-130°C and kept warm for reaction for 3-4 hours, after the reaction is completed, the product is transferred to another container, a mixed surfactant is added, and the mixture is stirred evenly to obtain the product; The mass ratio of ε-caprolactone to butyl methacrylate is (3-3.5): (2-4); The mixed surfactant is a mixture of alkyl glycoside and fatty alcohol polyoxyethylene ether; The mass ratio of the alkyl glycoside to the fatty alcohol polyoxyethylene ether is (2-3): (1-1.5); The fatty alcohol polyoxyethylene ether is cetearyl alcohol polyoxyethylene ether; The hydroxyl value of the cetearyl alcohol polyoxyethylene ether is 110-150 mgKOH / g.
2. A method for preparing the degradable tape according to claim 1, characterized in that: S1: Add the raw materials of the degradable base layer into a high-speed mixer and stir and mix them evenly. Then, add the mixed materials into an internal mixer for internal mixing and plasticization. Then, plasticize them through an extruder, calender and form them at 180-220°C, and cool and divide them to obtain a degradable base layer of the required thickness. S2: Add methyl methacrylate, ethyl acrylate, isooctyl acrylate and solvent into a reactor and stir and mix them thoroughly. Then, add functional monomers, emulsifiers, salt-forming agents and initiators into the reactor in sequence and mix and stir. Heat the reactor to 60-80°C, stir and keep warm for 3-5 hours, and finally neutralize and demulsify to obtain a degradable adhesive. S3: Spray the degradable adhesive on the surface of the release layer, form a degradable adhesive layer after drying, curing and aging, and compound the degradable adhesive layer with the degradable base layer to obtain a degradable tape.
3. An application of the degradable tape according to claim 1 in the fields of express logistics, food packaging, office stationery, electronic manufacturing, and disposable products.
Citation Information
Patent Citations
Ultrahigh-viscosity acrylate emulsion pressure-sensitive adhesive and preparation method thereof
CN111187586A
Preparation method of degradable PVC film and adhesive tape
CN116355327A